Estudio de la actividad microbiana durante el proceso de fermentación en híbridos de cacao (Theobroma cacao L.) mediante la adición de musáceas. - Rivera Benites, Gina Aidee (2017)
The objective of scientific research is the evaluation of microbial activity by adding two sources as energy source during the fermentation process of almonds in experimental cocoa (Theobroma cacao L.) hybrids. The evaluation was carried out in the Laboratory of Nutrition Rumiology and Metabolism (RUMEN) of the Experimental Farm "La María", belonging to Quevedo State Technical University of Los Ríos province, during a field period of approximately one month (January). (DCA) with a 2x4 factorial arrangement, performing the Tukey test at 5% probability, eight treatments and four replications were managed, with hybrids (DIRCYT-258, 259, 263 and 265) as the A factor, Y as Factor B The plants (Banana puree and banana), 576 experimental units were handled for the fermentation time of cocoa (24, 48 and 72 hours), as well as 10% mass of the musaceae for the fermentation process. 10-3 decimal solution for the sowing of the evaluated microorganisms (lactic acid bacteria, acetic acid and yeast), the results showed interaction to raise during the 48 hours of starting the fermentation process with respect to the colony forming units UFC g -1, whereas for acidic and acetic bacteria, it was not significant during the time evaluated as these were kept in tandem with the microbial population, conclude that the addition of two ways as they were Of energy during the fermentation process of almonds in hybrid cocoa experiments did not generate an increase in the number of colony forming units UFC g -1 during the fermentation process.